1995
DOI: 10.1523/jneurosci.15-04-03215.1995
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of human MT and related visual cortical areas using magnetic resonance imaging

Abstract: Using noninvasive functional magnetic resonance imaging (fMRI) technique, we analyzed the responses in human area MT with regard to visual motion, color, and luminance contrast sensitivity, and retinotopy. As in previous PET studies, we found that area MT responded selectively to moving (compared to stationary) stimuli. The location of human MT in the present fMRI results is consistent with that of MT in earlier PET and anatomical studies. In addition we found that area MT has a much higher contrast sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

116
825
5
7

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,318 publications
(953 citation statements)
references
References 103 publications
116
825
5
7
Order By: Relevance
“…Functional imaging studies in humans have shown that the human homologue, area MT/V5, is also highly responsive to visual motion stimuli (Zeki et al 1991;Watson et al 1993;Tootell et al 1995). We found that MT/V5 was bilaterally more activated in the reXexive than in the voluntary saccade condition, although no real visual motion was present in either condition.…”
Section: Motion-sensitive Area (Mt/v5)mentioning
confidence: 50%
“…Functional imaging studies in humans have shown that the human homologue, area MT/V5, is also highly responsive to visual motion stimuli (Zeki et al 1991;Watson et al 1993;Tootell et al 1995). We found that MT/V5 was bilaterally more activated in the reXexive than in the voluntary saccade condition, although no real visual motion was present in either condition.…”
Section: Motion-sensitive Area (Mt/v5)mentioning
confidence: 50%
“…variation of Michelson contrast), showing that BOLD signal increases non-linearly with contrast (see also (Tootell et al, 1995)) whilst beta band power loss during stimulation was approximately equal regardless of visual contrast. This was in contrast to the visual gamma band response, which increased monotonically with stimulus contrast, (see also ).…”
Section: Temporal and Spectral Relationshipsmentioning
confidence: 89%
“…(Tanaka, 1996). Regions in the dorsal stream corresponding to areas MT and MST in the monkey, dubbed "the MT complex" (MT +), selectively represent features of object and observer movement (Tootell, et al, 1995). Adjacent areas in the posterior superior temporal sulcus (pSTS) are selectively activated by nonrigid biological motion (Grossman, et al, 2000;Beauchamp, Lee, Haxby, & Martin, 2003).…”
Section: Neural Correlates Of Event Segmentationmentioning
confidence: 99%